Respuesta :
As a fact:
h(f(x)), if h is the inverse function of f(x), that is f⁻¹
f⁻¹(f(x)) = x
C
h(f(x)), if h is the inverse function of f(x), that is f⁻¹
f⁻¹(f(x)) = x
C
Answer:
x
Step-by-step explanation:
If h(x) is the inverse of f(x), what is the value of h(f(x)
For example , [tex]f(x)= x+6[/tex]
Lets find the inverse of f(x), replace f(x) with y
[tex]y=x+6[/tex]
Replace x with y and y with x
[tex]x=y+6[/tex]
Subtract 6 on both sides
[tex]x-6=y[/tex]
Replace y with h(x)
[tex]h(x) = x-6[/tex]
LEts find h(f(x))
[tex]h(f(x))= h(x+6)= (x+6)-6 = x[/tex]
IF h(x) is the inverse of f(x) then [tex]h(f(x))= x[/tex]